GAMPONG EMPLOYMENT INSURANCE AGREEMENT REVIEW ACCORDING TO KAFALAH AGREEMENT (Case Study of Riseh Tunong Village, Sawang District North Aceh Regency) - Ridwan Nurdin; Rita Purnamasari; Faisal Fauzan (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2021)
The Employment Social Security Administration (BPJS) is the responsibility and obligation of the State that focuses on social security and labor protection in Indonesia to provide socio-economic protection to the community by organizing Work Accident Insurance (JKK), Death Insurance (JKM), Old Age Security programs (JHT), and Retirement. In accordance with the state's financial capacity. With the existence of BPJS for Employment, it is proper to help workers who are at risk and get the compensation or services that should be obtained. In this case the Gampong apparatus is required to become a participant of BPJS Employment in accordance with the Gampong's financial capacity. Riseh Tunong Village apparatus, Sawang District, North Aceh Regency, participated in two social security programs, namely the JKK and JKM programs. The contribution is calculated based on the percentage of wages/salaries per month, representatives from the Gampong apparatus will pay all other village equipment fees to the Lhokseumawe BPJS Employment office, the contributions are taken from the Gampong Revenue and Expenditure Budget (APBG). The purpose of this study was to determine the system of agreement and BPJS employment insurance benefits for the Gampong Riseh Tunong apparatus, Sawang District, North Aceh Regency. And to find out the review of the kafalah contract in the insurance agreement on BPJS employment on the Riseh Tunong Village apparatus, Sawang District, North Aceh Regency. This research is qualitative with descriptive analysis research type, namely the author uses field research methods and library research methods. The results of the study show that the substance of BPJS Employment is the same as conventional insurance. This is because there are two things that are not in accordance with sharia in the scheme that occurs in BPJS Employment, namely the element of transfer of risk (uncertainty) and interest-bearing loans in the determination of contributions.